Molecular aspects of transferrin expression in the tsetse fly (Glossina morsitans morsitans) - Guz, Nurper (2007)
Iron is an essential element for metabolic processes intrinsic to life, and yet the properties that make iron a necessity also make it potentially deleterious. To avoid harm, iron homeostasis is achieved via proteins involved in transport and storage of iron, one of which is transferrin. We describe the temporal and spatial aspects of transferrin (GmmTsf) expression and its transcriptional regulation in tsetse where both the male and female are strictly hematophagous. Using Northern, Western and immunohistochemical analysis, we show that GmmTsf is abundant in the hemolymph and is expressed in the adult developmental stages of male and female insects. It is preferentially expressed in the female milk gland tubules and its expression appears to be cyclical and possibly regulated in synchrony with the oogenic and/or larvigenic cycle. Although no mRNA is detected, GmmTsf protein is present in the immature stages of development, apparently being transported into the intrauterine larva from the mother via the milk gland ducts. Transferrin is also detected in the vitellogenic ovary and the adult male testes, further supporting its classification as a vitellogenic protein. Similar to reports in other insects, transferrin mRNA levels increase upon bacterial challenge in tsetse suggesting that transferrin may play an additional role in immunity. Although transferrin expression is induced following bacterial challenge, it is significantly reduced in tsetse carrying midgut trypanosome infections. Analysis of tsetse that have cured the parasite challenge shows normal levels of GmmTsf. This observation suggests that the parasite in competing for the availability of limited dietary iron may manipulate host gene expression.